Experimental study of polishing systems on surface roughness and color stability of novel bulk-fill composite resins - Seda Nur Karakaş; Sevde Gül Batmaz; Volkan Çiftçi; Cihan Küden (BMC Oral Health)
Abstract Objective This in vitro study aimed to investigate the effect of five polishing systems on the surface roughness (SR) and color change (CC) of novel bulk-fill composite resins. Methods Fifty composite resin samples were prepared for each of the five groups: Stark Bulk Fill, SDR Plus, SonicFill 3, Charisma Bulk Flow One, and Filtek Z250. Each group of composite resins was further subdivided into five subgroups based on the polishing method applied: OptraGloss (OG), OptraGloss combined with Diapolisher paste (OGD), OptiDisc (OD), OptiDisc combined with Diapolisher paste (ODD), and Occlubrush (OCC) (n = 10). Surface roughness was measured using a profilometer following the polishing procedures, while surface morphology was assessed through atomic force microscopy and scanning electron microscopy. Subsequently, the samples were divided into two further subgroups for aging in distilled water and coffee (n = 5). The initial color parameters and those measured after 7 days were recorded to evaluate color change. Statistical analysis was performed using two-way ANOVA, followed by Tukey’s post-hoc tests (α = 0.05). Results SR significantly varied based on the composite resin and polishing system (p < 0.001). OCC polishing yielded the smoothest surface for STARK and SDR composites, while Charisma exhibited the lowest roughness in the ODD group (p < 0.05). OGD group consistently produced lower SR across multiple composites compared to the OG group (p < 0.001). Significant color changes (ΔE00) were found, with SonicFill and Filtek showing the greatest color stability when polished with OGD and OCC. For all polishing systems, except ODD, the SDR composite showed the greatest CC in coffee storage (p < 0.003). Conclusion This study demonstrated that both the polishing technique and composite resin type significantly influenced SR. SR was notably affected by the interaction between the polishing method and resin type, with the OCC system consistently producing the lowest SR values. Additionally, Charisma exhibited surface properties similar to Filtek. Variations in color change were also observed based on both the polishing method and resin type, highlighting the critical role these factors play in determining the color stability of restorative materials.